Implementasi Pendidikan Akhlak Dalam Mata Pelajaran PAI Pada Siswa Siswi Di MAS Al-Asyariyah Medan Krio - Nurmala Samin; Abdurrasyid Abdurrasyid (Yayasan Rahmat Islamiyah, 2025)
Character education is an important part of the formation of noble morals in students. In Islamic religious education, character education is very important to shape attitudes, behavior, and morals in accordance with Islamic values. This research aims to: 1. Analyze how the application of character education in PAI subjects to improve student morale. 2. Analyzing the strategy and effectiveness of the application of character education in PAI subjects in improving student morals. This research method uses a qualitative descriptive approach, focusing on the development of PAI curriculum that emphasizes character values. Data collection techniques were carried out using the methods of interview, observation, and documentation. The results of the researchers' initial observations showed that strengthening moral values through PAI can create a positive learning environment and support students' moral development.